OPTIMIZATION OF LEARNING WITH SCHOOLOGY FOR BEST PRACTICES IN QUALITY OF LEARNING OUTCOMES - Satria Mihardi; Derlina ,; Alkhafi Maas Siregar; Abd Hakim S (Jurnal Pendidikan Fisika, 2022)
The expected learning outcomes in pandemic learning are very different and need to be emphasized on certain things. Various ways are done by adding media, learning management systems, and learning aids are expected to help students learn something new. The new experiences learned will be important information for students to be able to develop their abilities. E-learning is an innovation that can be utilized in the learning process, not only in the delivery of learning materials but also in changes in the abilities of various student competencies. E-learning is an educational system that uses information technology in the teaching and learning process that can be done anywhere and anytime because the learning materials can be accessed remotely. The analysis used uses a survey system of qualitative data that describes the percentage of the use of several Learning Management Systems (LMS). This is done to determine the optimization of learning carried out with various LMS. There are 3 LMS used, namely: local LMS (SIPDA); Schoology; and Google Classroom. The three LMS will be used as material for comparison of user responses in learning Physics. This assessment is based on the use of the appropriate features of the three LMS. The picture shows the acceptance of respondents to Schoology reaching 90%. This seems to have a difference of around 20%-30% compared to the other two LMS. This shows that Schoology is more familiar with the features needed in e-learning. This makes it easy for users. Schoology is more ready to be used as an e-learning-based Physics learning platform.